Erythroid precursors regulate local oxygen tension and repair outcomes in the bone marrow niche - Annemarie Lang; Joseph M. Collins; Madhura P. Nijsure; Simin Belali; Mohd Parvez Khan; Yasaman Moharrer; Ernestina Schipani; Yvette Y. Yien; Yi Fan; Michael Gelinsky; Sergei A. Vinogradov; Cameron Koch; et al. (Proceedings of the National Academy of Sciences, 2025)
Oxygen tension dynamically regulates stem cell fate and tissue regeneration, yet how local oxygen availability is controlled within the bone marrow niche remains poorly understood. While bone marrow injury, such as by bone fracture, disrupts marrow vasculature, the consequences for local oxygen tension remain unclear. Here, we show in mice that while the tissue oxygen tension in bone marrow is low (25 mmHg, ~4% O 2 ), intracellular oxygenation is heterogeneous, and erythroid cells are high in oxygen. Bone fracture elevates oxygen tension in the injured bone marrow (>55 mmHg, ~8%), which persists for over a week postinjury. This oxygen elevation results not from angiogenesis, but rather from localized expansion of erythroid precursor cells in the injured bone marrow. Injury-activated erythroid precursors synthesize hemoglobin and concentrate oxygen at the injury site; however, blocking transferrin receptor 1 (CD71)-mediated iron uptake impairs hemoglobin synthesis, reduces local oxygen levels, and enhances bone regeneration through increased angiogenesis and osteogenesis. Together, these findings identify erythroid precursors as active regulators of local oxygen availability in the bone marrow niche, which may be targetable to enhance tissue regeneration.